2016
DOI: 10.1080/09637486.2016.1195798
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic chromatographic fingerprint study of short-chain fatty acids in human milk, infant formula, pure milk and fermented milk by gas chromatography–mass spectrometry

Abstract: Human milk, infant formula, pure milk and fermented milk as food products or dietary supplements provide a range of nutrients required to both infants and adults. Recently, a growing body of evidence has revealed the beneficial roles of short-chain fatty acids (SCFAs), a subset of fatty acids produced from the fermentation of dietary fibers by gut microbiota. The objective of this study was to establish a chromatographic fingerprint technique to investigate SCFAs in human milk and dairy products by gas chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…According to the authors, the addition of mixed starter cultures may result in a partial inhibition of lipoprotein lipase activity [33], suggesting that the use of a specific bacterial strain, rather than another, may be a useful tool to increase the nutritional value of fermented products. Another research group analyzed different samples of human milk, commercial pure cow milk, infant formula and fermented cow milk, finding highest amount of SCFAs in fermented cow milk [34]. In line with this evidence, a further study demonstrated that the fermentation of skimmed milk with Lactobacilli or Bifidobacteria increased SCFA production with variable trends, based on the type of added prebiotics, including β-glucan, inulin and hi-maize.…”
Section: Increased Levels Of Scfas In Fermented Foods and Beveragesmentioning
confidence: 79%
See 1 more Smart Citation
“…According to the authors, the addition of mixed starter cultures may result in a partial inhibition of lipoprotein lipase activity [33], suggesting that the use of a specific bacterial strain, rather than another, may be a useful tool to increase the nutritional value of fermented products. Another research group analyzed different samples of human milk, commercial pure cow milk, infant formula and fermented cow milk, finding highest amount of SCFAs in fermented cow milk [34]. In line with this evidence, a further study demonstrated that the fermentation of skimmed milk with Lactobacilli or Bifidobacteria increased SCFA production with variable trends, based on the type of added prebiotics, including β-glucan, inulin and hi-maize.…”
Section: Increased Levels Of Scfas In Fermented Foods and Beveragesmentioning
confidence: 79%
“…Nevertheless, authors generally agree that fermentation significantly increases the levels of this class of bioactive compounds ( Table 1 ). Different raw materials have been studied, including milk [ 32 , 33 , 34 ], beer wort [ 35 ], fruit [ 36 ] and vegetables [ 2 ], and several bacteria strains have been used for fermentation.…”
Section: Increased Levels Of Scfas In Fermented Foods and Beveragementioning
confidence: 99%
“…Short chain fatty acids (SCFAs) are produced by intestinal commensal bacteria interacting with a diet rich in complex carbohydrates which cannot be metabolized by enzymes in the small intestine [9]. In the immature human intestine, SCFAs are produced when expressed breastmilk fed to prematures interacts with colonizing bacteria [10,11] for example, Bifidobacteria infantis can produce increased levels of SCFAs (acetate, propionate and butyrate) [12]. A number of studies in mature intestine have shown that SCFAs have anti-inflammatory effects under conditions of intestinal inflammation such as dextran sulfate sodium (DSS) colitis and are in short supply in patients with inflammatory bowel disease and rheumatoid arthritis [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…HM samples (2 mL) were collected at the beginning of lactation by either manual or electric breast pump into sterile tubes, as previously described. 18 Samples were immediately frozen and then stored at −80°C until analysis. For each enrolled subject, anamnestic, demographic, clinical, and laboratory data were recorded in a data collection sheet.…”
Section: Methodsmentioning
confidence: 99%